1992
DOI: 10.1161/01.res.71.2.471
|View full text |Cite
|
Sign up to set email alerts
|

Impaired myogenic responsiveness of renal microvessels in Dahl salt-sensitive rats.

Abstract: The mechanisms mediating abnormal renal autoregulation in Dahl salt-sensitive (DS) rats have not been fully defined. In the present study, we assessed myogenic responsiveness of interlobular arteries (ILAs), afferent arterioles (AAs), and efferent arterioles in isolated perfused hydronephrotic Dahl rat kidneys. Dahl rats were divided into four groups according to strain (Dahl salt-resistant [DRI or the development of hypertension in DS rats. We have also demonstrated that in DS rats an impairment of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 19 publications
6
61
0
Order By: Relevance
“…It also modulates tubuloglomerular feedback responsiveness, probably by affecting vascular reactivity to adenosine through modulation of K Ca channel activity (45). Indeed, this hypothesis is consistent with previous observations that the myogenic response (37) and dynamic autoregulation of RBF is impaired in Dahl S rats (14) and that TGF responsiveness is decreased when these rats are fed a HS diet (40).…”
Section: Discussionsupporting
confidence: 88%
“…It also modulates tubuloglomerular feedback responsiveness, probably by affecting vascular reactivity to adenosine through modulation of K Ca channel activity (45). Indeed, this hypothesis is consistent with previous observations that the myogenic response (37) and dynamic autoregulation of RBF is impaired in Dahl S rats (14) and that TGF responsiveness is decreased when these rats are fed a HS diet (40).…”
Section: Discussionsupporting
confidence: 88%
“…47 These alterations in zonal hemodynamics within the kidney may be able to explain the observation that glomerular sclerosis is seen primarily in the juxtamedullary nephrons in SHR, despite the fact that whole kidney autoregulation is well preserved and the degree of total renal damage is much less than that seen in other hypertensive models, such as in Ang II-induced hypertension and Dahl salt-sensitive hypertensive rats. [48][49][50][51][52][53] The study of Mori et al 34 in Ang II-induced hypertension gives a strong support to the concept that hypertension itself causes tissue injuries primarily in the juxtamedullary cortex and outer medulla. Using the servo-control method, they kept perfusion pressure to the left kidney at a normotensive level, while inducing systemic hypertension by intravenous infusion of Ang II.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 89%
“…[25][26][27] It has also been shown that the myogenic responsiveness in DS rats is diminished. 28 Karlsen et al 29 reported that tubuloglomerular feedback responsiveness in hypertensive DS rats remained intact, which was not attenuated, as might be expected with reductions of intrarenal Ang II levels. Thus, these pathophysiological characteristics of intrarenal function in DS rats are consistent with an inappropriately enhanced AGT in the kidney, which may contribute to the development and maintenance of hypertension.…”
Section: Kobori Et Al Angiotensinogen In Dahl Rats 595mentioning
confidence: 90%